2004
DOI: 10.1139/s04-012
|View full text |Cite
|
Sign up to set email alerts
|

Near-bed hydrodynamic measurements above boulders in shallow torrential streams: Implications for stream biota

Abstract: The near-bed hydraulic environment inhabited by torrential stream fauna was characterized by recording velocity profiles, near-bed velocities, and local wall shear stresses over the upper surface of boulders (or stones) in a mountain stream located in eastern British Columbia. Velocity profiles regularly deviated from a semi-logarithmic shape, and were often found to be "wedge-shaped", due likely to near-bed acceleration resulting from flow constriction over the leading edge of the stones. Local bed shear stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 33 publications
5
25
1
Order By: Relevance
“…demonstrated that nearly 75% of the variance of turbulent fluctuations can be attributed to the larger turbulent flow structures. This is consistent with observations of eddy shedding from particles and clusters that is significant locally (Buffin-Bélanger et al, 2006;, and modifies local velocity profiles causing boundary shear stress above that predicted by the log-law (Hoover and Ackerman, 2004), but does not affect larger scale turbulent flow structures in a reach.…”
Section: Gravel Bedssupporting
confidence: 90%
“…demonstrated that nearly 75% of the variance of turbulent fluctuations can be attributed to the larger turbulent flow structures. This is consistent with observations of eddy shedding from particles and clusters that is significant locally (Buffin-Bélanger et al, 2006;, and modifies local velocity profiles causing boundary shear stress above that predicted by the log-law (Hoover and Ackerman, 2004), but does not affect larger scale turbulent flow structures in a reach.…”
Section: Gravel Bedssupporting
confidence: 90%
“…In addition to the drag force, the shear stress in near-bed region can also be used to represent the flow resistance. Hoover and Ackerman (2004) measured local shear stress with the Preston-static tube (PST), and the results were similar to those calculated from the wall function in which velocity profiles presented logarithmic distributions. They also believed that both stream bed and water surface topography exerted influence on wedge-shaped velocity profiles and shear stress.…”
Section: Introductionsupporting
confidence: 65%
“…The universal velocity profile function can actually be written as U = f (y, Re, k s ), where f is a universal non-dimensional function to be determined and k s is the parameter representing the local bed configuration. Under complex landform conditions, e.g., intense particle projection (Ferro 2003a), vegetation (Huai et al 2009) and a small ratio of flow depth to roughness height (Hoover and Ackerman 2004), the situation should be paid particular attention. Figure 4 depicts the velocity profiles in groups 3 and 4 with identical sediment particles and with various flow conditions.…”
Section: Velocity Profilesmentioning
confidence: 99%
“…To overcome these challenges may ultimately require instruments with fine spatial resolution to measure basic hydraulic parameters (Carling 1992, Hoover andAckerman 2004). This complexity, with associated gradients of velocities over small distances, may be one reason why we found no significant correlations between average water column velocities measured using a mini current meter, and those estimated closer to the boundary layer using indirect techniques.…”
Section: Characterisation Of Hydraulic Habitatmentioning
confidence: 83%